6Li210B4O7 NPs-loaded plastic scintillators for fast/thermal neutron and gamma ray detection. (4th June 2019) - Frangville, Camille; Grabowski, Amélie; Dumazert, Jonathan; Montbarbon, Eva; Lynde, Clément; Coulon, Romain; Venerosy, Amélie; Bertrand, Guillaume H. V.; Hamel, Matthieu
Abstract : We report herein the synthesis of a new series of plastic scintillators (PSs) loaded with 6 Li2 10 B4 O7 nanoparticles (NPs), as new radioluminescent sensors for fast/thermal neutron and gamma ray detection in the critical context of homeland security. Abstract : We report herein the synthesis of a new series of plastic scintillators (PSs) loaded with 6 Li2 10 B4 O7 nanoparticles (NPs), as new radioluminescent sensors for fast/thermal neutron and gamma ray detection in the critical context of homeland security. This study aims to evaluate the benefit of such nanoparticles towards thermal neutron detection in a fast neutrons/gamma discriminating PS composition. First, a size-controlled synthesis of Li2 B4 O7 NPs assited with poly( N -vinylpyrrolidone) (PVP) is performed. Then enriched 6 Li2 10 B4 O7 NPs (65 ± 22 nm) are dispersed in clear PSs mainly composed of polystyrene and standard fluorophores (20 wt% PPO, 0.03 wt% POPOP). For the first time, a triple n thermal / n fast /gamma discrimination is presented with a NP-loaded plastic scintillator, where both 6 Li(n, α) and 10 B(n, α) are observed.